Dengue Fever in Italy: The “Eternal Return” of an Emerging Arboviral Disease - Matteo Riccò; Simona Peruzzi; Federica Balzarini; Alessandro Zaniboni; Silvia Ranzieri (Tropical Medicine and Infectious Disease, 2022)
Enhanced surveillance for dengue virus (DENV) infections in Italy has been implemented since 2012, with annual reports from the National Health Institute. In this study, we summarize available evidence on the epidemiology of officially notified DENV infections from 2010–2021. In total, 1043 DENV infection cases were diagnosed, and most of them occurred in travelers, with only 11 autochthonous cases. The annual incidence rates of DENV infections peaked during 2019 with 0.277 cases per 100,000 (95% confidence interval [95% CI] 0.187–0.267), (age-adjusted incidence rate: 0.328, 95% CI 0.314–0.314). Cases of DENV were clustered during the summer months of July (11.4%), August (19.3%), and September (12.7%). The areas characterized by higher notification rates were north-western (29.0%), and mostly north-eastern Italy (41.3%). The risk for DENV infection in travelers increased in the time period 2015–2019 (risk ratio [RR] 1.808, 95% CI 1.594–2.051) and even during 2020–2021 (RR 1.771, 95% CI 1.238–2.543). Higher risk for DENV was additionally reported in male subjects compared with females subjects, and aged 25 to 44 years, and in individuals from northern and central Italy compared to southern regions and islands. In a multivariable Poisson regression model, the increased number of travelers per 100 inhabitants (incidence rate ratio [IRR] 1.065, 95% CI 1.036–1.096), the incidence in other countries (IRR 1.323, 95% CI 1.165–1.481), the share of individuals aged 25 to 44 years (IRR 1.622, 95% CI 1.338–1.968), and foreign-born residents (IRR 2.717, 95% CI 1.555–3.881), were identified as effectors of annual incidence. In summary, although the circulation of DENV remains clustered among travelers, enhanced surveillance is vital for the early detection of human cases and the prompt implementation of response measures.